Recent Advances in Lupus B Cell Biology: PI3K, IFNγ, and Chromatin - Bacalao, Maria A.; Satterthwaite, Anne B. (Frontiers in Immunology, 2021)
In the autoimmune disease Systemic Lupus Erythematosus (SLE), autoantibodies are formed that promote inflammation and tissue damage. There has been significant interest in understanding the B cell derangements involved in SLE pathogenesis. The past few years have been particularly fruitful in three domains: the role of PI3K signaling in loss of B cell tolerance, the role of IFNg signaling in the development of autoimmunity, and the characterization of changes in chromatin accessibility in SLE B cells. The PI3K pathway coordinates various downstream signaling molecules involved in B cell development and activation. It is governed by the phosphatases PTEN and SHIP-1. Murine models lacking either of these phosphatases in B cells develop autoimmune disease and exhibit defects in B cell tolerance. Limited studies of human SLE B cells demonstrate reduced expression of PTEN or increased signaling events downstream of PI3K in some patients. IFNg has long been known to be elevated in both SLE patients and mouse models of lupus. New data suggests that IFNgR expression on B cells is required to develop autoreactive germinal centers (GC) and autoantibodies in murine lupus. Furthermore, IFNg promotes increased transcription of BCL6, IL-6 and T-bet in B cells, which also promote GC and autoantibody formation. IFNg also induces epigenetic changes in human B cells. SLE B cells demonstrate significant epigenetic reprogramming, including enhanced chromatin accessibility at transcription factor motifs involved in B cell activation and plasma cell (PC) differentiation as well as alterations in DNA methylation and histone modifications. Histone deacetylase inhibitors limit disease development in murine lupus models, at least in part via their ability to prevent B cell class switching and differentiation into plasma cells. This review will discuss relevant discoveries of the past several years pertaining to these areas of SLE B cell biology.